Low power consumption nonlinear control with H? compensator for a zero-bias flywheel AMB system - Sivrioglu, S; Nonami, K; Saigo, M (Sage Publications Ltd, 2004)
A nonlinear control approach based on a control current switching rule is studied experimentally for an energy storage flywheel active magnetic bearing (AMB) system. In the proposed control, only one electromagnet in each axis of the AMB has a current flow at any given time, depending on the rotor displacement. This results in a power consumption that is lower than a linear control employing a bias current. The equation of motion for the rigid rotor-AMB system is transformed to have a decentralized structure for the control design. To compute nonlinear control currents, an Hinfinity compensator is designed for each axis of the AMB. The proposed approach is experimentally verified using a high-speed digital signal processor.
Keywords: nonlinear control; zero-bias AMB; H(infinity) control design; flywheel system